Cosimulation of vehicle dynamics and terrain interaction to predict one-pass vehicle cone index. Issue 1 (2019) - Goodin, Christopher T.; McKinley, George B.; Cummins, Christopher L.; Priddy, Jody D.
The one-pass vehicle cone index (VCI1 ) is a measurement of the softest soil over which a vehicle can consistently drive at least once. In the last few decades, VCI1 has become a common quantitative indicator for the soft-soil performance of wheeled and tracked ground vehicles. Because VCI1 depends on not only the strength (as measured by Cone Index) of the soil but also the type of the soil, it is difficult to numerically predict VCI1 for notional ground vehicles. While reliable empirical methods to predict VCI1 have been refined over the years, the emergence of new vehicle technologies such as traction control systems presents a new challenge for ground vehicle modelling and necessitates a new way for predicting VCI1 performance. In this paper, we present accurate numerical predictions of VCI1 that use the Chrono multi-body dynamics code for vehicle dynamics, cosimulated with empirical, dynamic traction predictions at the vehicle-terrain interface by using the Ground Contact Element (GCE) code. We show that this cosimulated approach accurately reproduces measured values for a variety of wheeled vehicles.